PENGENALAN ALAT MUSIK TRADISIONAL BENGKULU (DOL) DIGITAL BERBASIS ANDROID - yovi apri apridiansyah; Pahrizal Pahrizal (JTIS: Journal of Technopreneurship and Information System, 2019)
Abstract—. Indonesia possesses a highly diverse affluence of art and culture, from Sabang to Merauke, deployed in a variety of arts and cultures that have been bequeathed from generation to generation. Dol is a traditional musical instrument that is performed by striking, which is based on electroacoustic technology or digital methods. His tone is harked through an amplifier and loudspeaker. In terms of sound quality, electronic dol practically makes no difference with common dol. Based on the background, the problem was formulated on how to make a recognition to traditional musical instruments (dol) built upon Android. The research objective of introducing traditional musical instruments (dol) on Android-based digital is to append concept into learning virtual dol with Android so that it is increasingly interactive. The costs of this application is that it is not mobile in 3 dimensions, in dol and tasa voice recording settings still utilizing normal recording.Keywords: Application, Music, Dol, AndroidAbstrak—. Indonesia memiliki kekayaan seni dan budaya yang sangat beragam, dari Sabang sampai Merauke, tersebar beraneka ragam seni dan budaya yang diwariskan secara turun temurun. Dol adalah alat musik tradisional yang dimainkan dengan dipukul, yang didasarkan pada teknologi elektroakustik atau metode digital. Nada suaranya terdengar melalui sebuah amplifier dan loudspeaker. Dari sisi mutu suara, dol elektronik nyaris tak ada bedanya dengan dol biasa. Berdasarkan latar belakang, maka dirumuskan masalahnya bagaimana membuat pengenalan alat musik tradisional (dol) digital berbasis android. Tujuan penelitian pengenalan alat musik tradisional (dol) digital berbasis android adalah untuk menambah wawasan dalam belajar dol virtual dengan android sehingga yang lebih interaktif. Kekurangan aplikasi ini tidak bersifat 3 dimensi yang berbasis mobile, dalam pengaturan perekaman suara dol dan tasa masih menggunakan perekaman biasa.Kata Kunci : Aplikasi, Musik, Dol, Android